(untitled) (Research, Society and Development, 2022)
According to researchers, the transition of all students from primary to secondary education represents a passage, a challenging change, but also an opportunity for change with consequences for the student’s cognitive, emotional, and psychosocial areas of development. This transition also happens to coincide with the person’s critical developmental stage, the start of adolescence. The issue is tackled from a multidisciplinary perspective and affects a large number of teachers, parents, psychologists, specialist educators, and most importantly the kids themselves. This study conducts a bibliographic assessment of the literature on the transitions of individuals with special educational needs, the challenges they encounter, and the contribution of ICT to a successful transfer. from the general or special school units of Primary Education in the comparable secondary school units Education.